Japan's Nuclear Crisis The Routes to Responsibility - Carpenter, S. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
An analysis and exploration into the impact of Japan's 2011 nuclear crisis. Investigation of the disaster will pose questions regarding why Daiichi was constructed in an earthquake-prone zone and was still operating despite problems that had been plaguing the reactors since 1989 such as cracks in infrastructure and leaks in radioactivity.